Peningkatan Mutu Pendidikan Hindu Melalui Pengelolaan Pembelajaran - I Putu Widyanto (Jurnal Penjaminan Mutu, 2020)
Hindu Education Institution is one of Education Institution which has responsibility in establishing and improving Hindu’s Human Resource quality to obtain competitiveness in facing globalization challenge. In the process of Hindu Education learning, still widely found the educator using Teacher-Centered Learning Approach which is makes students less actively involved in the learning process. This research aims to generate a synthesis concerning Hindu Education Learning management which can accomplish the qualification of graduate abilities which has been determined by the government. The study uses a qualitative research approach to the type of library research. The existence of Hindu education, in it’s role of engender the young Hindu generation who is ready to deal with global challenge, should be able to organize the process of debriefing with presenting education which integrate intellectuality, creativity, spirituality, and morality in its education system, and refer to the Hindu value with applying the Student-Centered Learning approach alongside learning management principal.